Experts and Consensus in Social Science - Martini, Carlo; Boumans, Marcel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book brings together the research of philosophers and social scientists. It examines those areas of scientific practice where reliance on the subjective judgment of experts and practitioners is the main source of useful knowledge to address, and, possibly, bring solutions to social problems. A common phenomenon in applications of science is that objective evidence does not point to a single answer, or solution, to a problem. Reliance on subjective judgment, then, becomes necessary, despite the known fact that hunches, even those of putative experts, often provide information that is not very accurate, and that experts are prone to fallacies and biases. The book looks at how experts reach consensus in the social sciences, and which experts are relevant to which problems. This book offers the ingredients for building a normative theory of expertise on the basis of the evidence that social scientists and philosophers have uncovered.
Keywords: Philosophy (General).; Social sciences -- Philosophy; Economics -- Methodology; Social sciences -- Methodology; Philosophy; Philosophy of the Social Sciences; Methodology and the History of Economic Thought; Methodology of the Social Sciences